2013
DOI: 10.1186/2193-1801-2-592
|View full text |Cite
|
Sign up to set email alerts
|

Natural weathering studies of oil palm trunk lumber (OPTL) green polymer composites enhanced with oil palm shell (OPS) nanoparticles

Abstract: In this study, a green composite was produced from Oil Palm Trunk Lumber (OPTL) by impregnating oil palm shell (OPS) nanoparticles with formaldehyde resin. The changes of physical, mechanical and morphological properties of the OPS nanoparticles impregnated OPTL as a result of natural weathering was investigated. The OPS fibres were ground with a ball-mill for producing nanoparticles before being mixed with the phenol formaldehyde (PF) resin at a concentration of 1, 3, 5 and 10% w/w basis and impregnated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
8
0
9
Order By: Relevance
“…This leads to the deterioration in molecular weight and mechanical properties of the composites. The obtained results are in agreement with the earlier report by Nazrul Islam et al (2013), Silva et al (2017) and Zaaba et al (2015). Elongation at break is one of the most crucial tensile properties that are used when studying polymer degradation, as it can give an early indication of mechanical failure (Spinace & De Paoli 2015).…”
Section: Tensile Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…This leads to the deterioration in molecular weight and mechanical properties of the composites. The obtained results are in agreement with the earlier report by Nazrul Islam et al (2013), Silva et al (2017) and Zaaba et al (2015). Elongation at break is one of the most crucial tensile properties that are used when studying polymer degradation, as it can give an early indication of mechanical failure (Spinace & De Paoli 2015).…”
Section: Tensile Propertiessupporting
confidence: 92%
“…The photo-degradation due to the absorption of ultraviolet radiation induces the occurrence of polymer chain scission as well as the leaching of fibers components from the exposed sample surfaces (Azwa et al 2013;Nazrul Islam et al 2013). Composites with 40 phr KNF possess the highest weight loss percentage which can be attributed to the higher amount of KNF detached from composite surfaces.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Flaky PKS is normally used in the ground form and work as a natural filler for polymer composites. [9] For a purpose of preparation lightweight aggregates in concrete, PKS shells have been used as received without further grinding. [10] On the other hand, dried palm shell (DPS) is another neglected oil palm waste, which has plenty on palm field.…”
Section: Introductionmentioning
confidence: 99%
“…Various chemical modification techniques have been used to improve the decay and weather resistance of wood by blocking the hydroxyl groups of cell wall polymers. [10][11][12] Mohebby 8 demonstrated that substitution of the hydroxyl groups from the cell wall polymers by the acetyl groups might be effective, as the acetyl groups are not accessible to the microorganisms. Thus far, phenol formaldehyde (PF) impregnation into OPTL has been widely reported in many studies as a means of protecting against degradation.…”
Section: Introductionmentioning
confidence: 99%